2013
DOI: 10.1111/1552-6909.12232
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Perspectives on the Intersection of Safety and Informed Decision Making in Maternity Care

Abstract: Objective To explore maternity nurses' perceptions of women's informed decision making during labor and birth to better understand how interdisciplinary communication challenges might affect patient safety. Design Constructivist grounded theory. Setting Four hospitals in the Western United States. Participants Forty six (46) nurses and physicians practicing in maternity units. Methods Data collection strategies included individual interviews and participant observation. Data were analyzed using the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The results revealed that conflicts between team members influenced the decision‐making process in a critical situation. These results are congruent with the evidence presented by Lyndon, Zlatnik, and Wachter () and Jacobson, Zlatnik, Powell Kennedy, and Lyndon () that a challenge to effective interprofessional communication included differing professional views on childbirth management leading to conflict. In addition, differences in perceptions of risk can potentially result in miscommunication and increase the probability of inadequate care (Van Otterloo & Connelly, ).…”
Section: Discussionsupporting
confidence: 89%
“…The results revealed that conflicts between team members influenced the decision‐making process in a critical situation. These results are congruent with the evidence presented by Lyndon, Zlatnik, and Wachter () and Jacobson, Zlatnik, Powell Kennedy, and Lyndon () that a challenge to effective interprofessional communication included differing professional views on childbirth management leading to conflict. In addition, differences in perceptions of risk can potentially result in miscommunication and increase the probability of inadequate care (Van Otterloo & Connelly, ).…”
Section: Discussionsupporting
confidence: 89%
“…Jacobson et al 24 observed that some strategies labour nurses used for education and advocacy veered into paternalistic territory and risked creating confusion and emotional suffering for women. One of the conditions under which this occurred was nursing concern for safety, similar to our finding that nurses used their sense of risk to frame constraint of women's options.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of intrapartum care have found that midwives, physicians and nurses all experience safety concerns (Maxfield, Lyndon, Kennedy, O'Keeffe, & Zlatnik, 2013) and patients being put at risk due to a failure to listen to or respond to safety concerns (Lyndon et al, 2014). Furthermore, nurses perceived a risk of harmful interventions and lack of information to the woman giving birth (Jacobson et al, 2013). Another patient safety problem raised in intrapartum care is communication between nurses and physicians (Lyndon et al, 2012).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Maternal death due to pregnancy and childbirth is unusual and considered a major human tragedy (Nyfløt, Ellingsen, Yli, Øian, & Vangen, ). Research about patient safety in connection to childbirth often targets the neonate (Ashcroft, ; Millde Luthander, ), with fewer studies focusing on the woman giving birth (Jacobson, Zlatnik, Kennedy, & Lyndon, ; Sheldon et al, ).…”
Section: Introductionmentioning
confidence: 99%